Community of practice on socio-economic data - Kruseman, Gideon K. (International Maize and Wheat Improvement Center, 2017)
This presentation was given virtually by Gideon Kruseman (CIMMYT), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017